2022
DOI: 10.1002/lio2.857
|View full text |Cite
|
Sign up to set email alerts
|

Acute exacerbations of chronic rhinosinusitis: The current state of knowledge

Abstract: Objectives: Acute exacerbations of chronic rhinosinusitis (AECRS) are distinct from baseline symptomatology related to chronic rhinosinusitis (CRS). In this review, we seek to examine the literature on AECRS to synthesize the definition, epidemiology, pathophysiology, treatment, and impact of AECRS on CRS patients.Methods: A comprehensive narrative review of the scientific literature, identified by searching PubMed from inception through April 2022, was performed.Results: AECRS is defined in consensus guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Although antibiotics are frequently used for the treatment of acute exacerbation of chronic rhinosinusitis (AECRS), the data are inconclusive regarding their efficacy [ 20 ]. A single randomized control trial to date examined the use of antibiotics in AECRS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although antibiotics are frequently used for the treatment of acute exacerbation of chronic rhinosinusitis (AECRS), the data are inconclusive regarding their efficacy [ 20 ]. A single randomized control trial to date examined the use of antibiotics in AECRS.…”
Section: Discussionmentioning
confidence: 99%
“…These include over the counter medications such as decongestants, mucolytics, acupuncture and other complementary medicine therapy. Yet no studies exist on the use of these therapies in AECRS [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AECRS are currently defined in consensus guidelines as a transient worsening of symptoms that return to baseline symptoms, often requiring intervention with systemic corticosteroids or antibiotics 3,4 . Because of the inexact nature of this definition of AECRS, many previous research studies have used patient‐reported use of systemic antibiotics and corticosteroids for CRS as proxy measures for AECRS 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Because of the inexact nature of this definition of AECRS, many previous research studies have used patient-reported use of systemic antibiotics and corticosteroids for CRS as proxy measures for AECRS. 5,6 In a recent study by our group, which directly investigated patient experiences with AECRS using interviews and qualitative methodology, we proposed an evidencebased and patient-centered definition for AECRS as: "A flare up of symptoms beyond day-to-day variation to which a distinct negative impact on a patient's QOL or functionality can be attributed." 7 However, there remains a need to establish a duration criterion for the increased symptoms that defines the occurrence of an AECRS.…”
Section: Introductionmentioning
confidence: 99%